Label‐Free Phase Change Detection of Lipid Bilayers Using Nanoscale Diamond Magnetometry. Issue 4 (19th February 2021) - Ishiwata, Hitoshi; Watanabe, Hiroshi C.; Hanashima, Shinya; Iwasaki, Takayuki; Hatano, Mutsuko
Abstract: The nitrogen‐vacancy (NV) center in diamond is a quantum sensor with exceptional quality for highly sensitive nanoscale analysis of nuclear magnetic resonance (NMR) spectra and thermometry. In this study, nanoscale phase change detection of lipid bilayers is investigated utilizing ensemble‐averaged nuclear spin detection from small volume ≈(6 nm) 3, which is determined by the depth of the NV center. Analysis of nanoscale NMR signal confirms thickness of lipid bilayer to be 6.2 nm ± 3.4 nm with proton density of 65 protons per nm 3 on top of diamond sample. The result of the correlation spectroscopy from nanoscale volume is compared with the 2D molecular diffusion model constructed by Monte Carlo simulation combined with results from molecular dynamics (MD) simulation. There is a change in diffusion constant from 1.5 ± 0.25 nm 2 µs −1 to 3.0 ± 0.5 nm 2 µs −1 when the temperature changes from 26.5 to 36.0 °C. The results demonstrate that the multi‐parameter detection of changes in translational diffusion and temperature is possible in label‐free measurements using nanoscale diamond magnetometry. The method paves the way for label‐free imaging of cell membranes for understanding their phase composition and dynamics. Abstract : Diffusion constant of a lipid bilayer, a biological parameter that determines the dynamics of the lipid bilayer, is determined through nanoscale diamond magnetometry. Observation of the diffusion constant at different temperature reveals different phases of the lipid bilayer. The result builds a foundation for label‐free imaging of cell membranes for the observation of phase composition and dynamics that determine cellular functions.